Science in the Spanish and Portuguese Empires—1500–1800 - Iris Kantor (2015)
The recently published Science in the Spanish and Portuguese Empires—1500–1800 brings together fifteen articles as well as two essays that summarize the main arguments developed in the collection. Geared towards an Anglo-American university audience, the book reassesses the importance of the Iberian legacy for understanding the scientific revolutions of the modern age by giving greater weight to the different (and highly particular) ways of engaging in, communicating and theorizing science that were practiced under the scope of the Portuguese and Spanish empires. The organizers question the reductionist and depreciative views associated with Iberian scientific culture that still persist in the great historiographic narratives about the formation of modern science.